Aberrant O-GlcNAcylated Proteins: New Perspectives in Breast and Colorectal Cancer - Chaiyawat, Parunya; Netsirisawan, Pukkavadee; Svasti, Jisnuson; Champattanachai, Voraratt (Frontiers in Endocrinology, 2014)
Increasing glucose consumption is thought to provide an evolutionary advantage to cancer cells. Alteration of glucose metabolism in cancer influences various important metabolic pathways including the hexosamine biosynthesis pathway (HBP), a relatively minor branch of glycolysis. Uridine diphosphate N-acetylglucosamine (UDP-GlcNAc), an end product of HBP, is a sugar substrate used for classical glycosylation and O-GlcNAcylation, a post-translational protein modification implicated in a wide range of effects on cellular functions. Emerging evidence reveals that certain cellular proteins are abnormally O-GlcNAc modified in many kinds of cancers, indicating O-GlcNAcylation is associated with malignancy. Since O-GlcNAc rapidly on and off modifies in a similar time scale as in phosphorylation and these modifications may occur on proteins at either on the same or adjacent sites, it suggests that both modifications can work to regulate the cellular signaling pathways. This review describes the metabolic shifts related to the HBP which are commonly found in most cancers. It also describes O-GlcNAc modified proteins identified in primary breast and colorectal cancer, as well as in the related cancer cell lines. Moreover, we also discuss the potential use of aberrant O-GlcNAcylated proteins as novel biomarkers of cancer. + P. Chaiyawat and P. Netsirisawan contributed equally to this study